Incremental dynamic analysis for estimating seismic performance sensitivity and uncertainty. - Vamvatsikos, Dimitros (Earthquake engineering & structural dynamics.)
Incremental dynamic analysis (IDA) is presented as a powerful tool to evaluate the variability in the seismic demand and capacity of non-deterministic structural models, building upon existing methodologies of Monte Carlo simulationand approximate moment-estimation. A nine-story steel moment-resisting frame is used as testbed, employing parameterized moment rotation relationships with non deterministic quadrilinear backbones for the beam plastic hinges. The uncertain properties of the backbones include the yield moment, the post yield hardening ratio, the end of hardening rotation, the slope of the descending branch, the residual moment capacity and the ultimate rotation reached. IDA is employed to accurately assess the seismic performance of the model for any combination of the parameters by performing multiple nonlinear timehistory analyses for a suite of ground motion records. Sensitivity analyses on both the IDA and the static pushover level reveal the yield moment and the two rotational ductility parameters to be the most influential for the frame behavior. To propagate the parametric uncertainty to the actual seismic performance we employ (a) Monte Carlo simulation with latin hypercube sampling, (b) point estimate, and (c) first order second moment techniques, thus offering competing methods that represent different compromises between speed and accuracy. The final results provide firm ground for challenging current assumptions in seismic guidelines on using a median parameter model to estimate the median seismic performance and employing the well known square root sum of squares rule to combine aleatory randomness and epistemic uncertainty.